1998
DOI: 10.1038/678
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of horizontal cortical connections following skill learning

Abstract: Learning a new motor skill requires an alteration in the spatiotemporal pattern of muscle activation. Motor areas of cerebral neocortex are thought to be involved in this type of learning, possibly by functional reorganization of cortical connections. Here we show that skill learning is accompanied by changes in the strength of connections within adult rat primary motor cortex (M1). Rats were trained for three or five days in a skilled reaching task with one forelimb, after which slices of motor cortex were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
373
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 621 publications
(406 citation statements)
references
References 28 publications
22
373
2
3
Order By: Relevance
“…Increased spontaneous neuronal firing and synaptic efficacy induced by direct‐current stimulation may strengthen neuronal connectivity through long‐term potentiation‐like mechanisms41, 42, 43. These mechanisms may potentiate motor learning, which is also thought to depend on long‐term potentiation‐like plasticity occurring in the motor cortex44. Modulation of the motor network, including the primary motor cortex, premotor cortex, supplementary motor areas and basal ganglia, has been implemented in motor learning45 46.…”
Section: Discussionmentioning
confidence: 99%
“…Increased spontaneous neuronal firing and synaptic efficacy induced by direct‐current stimulation may strengthen neuronal connectivity through long‐term potentiation‐like mechanisms41, 42, 43. These mechanisms may potentiate motor learning, which is also thought to depend on long‐term potentiation‐like plasticity occurring in the motor cortex44. Modulation of the motor network, including the primary motor cortex, premotor cortex, supplementary motor areas and basal ganglia, has been implemented in motor learning45 46.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis for these 2 groups was kept separate because it has been previously reported that plastic changes can occur to different extent in supra-and infragranular layers. [19][20][21][30][31][32] Arc positive cells were clearly identifiable as a strong cytoplasmic staining that occasionally extended into the most proximal dendrites, and in most cases were observed in layers V/VI. All sections were manually counted at least 2 times (reported values are the average), with a margin of error of less than 5% between the 2 measurements, giving us confidence that the counting procedure was reproducible.…”
Section: Motor Learning and Sleep Intensity-hanlon Et Almentioning
confidence: 97%
“…[19][20][21] We asked whether SWA shows a local increase in the trained motor cortex after learning to reach. Moreover, we examined whether skilled reaching increases the expression of Arc and Fos, 2 activity-dependent proteins involved in motor learning, [22][23][24] and whether this activation is specific for the trained motor area relative to other cortical areas.…”
Section: Sleep Is Present and Homeostatically Regu-lated In All Animamentioning
confidence: 99%
“…Detectability means that there are changes at the synaptic level after an animal has learned or memorized something (e.g., Rioult-Pedotti et al, 1998;Whitlock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%